Separation and evaluation of natural antileishmanial potential against Leishmania major and infuntum isolated from the Tunisia strains - Bouabdallah, Salwa; Laouini, Dhafer; Bouzouita, Nabiha; El-Bok, Safia; Sghaier, Rabiaa M.; Selmi, Sawssen; Attia, Mossadok Ben (Bangladesh Journal of Pharmacology, 2018)
Besides its nutritional value as a dietary supplement, Tribulus terrestris is used as a remedy for fertility disorder in Ayurveda and Chinese medicine as well as by modern herbalists. The aim of this study was to explore the biological potential (antileishmanial effect) of an extract rich in saponins from Tunisian tribulus. The chloroform extract of the various parts of T. terrestris was subjected to partial purification by solvent partitioning with ethanol and n-butanol. All prepared extracts were tested for their anti-leishmanial activity. The result showed that n-butanolic extract (saponin fraction, when isolated from leaves part) exhibited the best antileishmanial effect against both pathogenic parasites Leshmania L. major (GlC94) and L. infuntum (LV50) evaluated in vitro assessment through MTT assay. n-Butanolic extract had been detected, quantified and purified using the RP-HPLC finger print (Hypersil ODS coupled to UV-vis). High peak area (5116.82 at 3.03 min) was detected at 205 nm.